Linking Agriculture and Ground Water Resources in Punjab (International Journal of Food and Nutritional Sciences, 2022)
With only 1.5% of the country's total land area, the state of Punjab has achieved significant growth in the agricultural industry, particularly in the area of food crops. Green revolution boosts the agriculture in the state. Punjab is known as the "breadbasket" of the country due to high production of food crops. To sustain the existing level of agricultural growth in mono-crops (rice-wheat) the natural resources are being overused. The state of Punjab is facing problem ofdepletion of ground water. The modern practices of agriculture has put a big question mark on the further use of ground water any more for agriculture. Through market incentives, some land must be converted to acceptable alternative crops, especially in areas where rice production is low. The promotion of drip irrigation and sprinkler systems should be a major focus in order to use water resources wisely.